Labor Relations Boards and the Courts - Weatherhill, J. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1966)
The Canada Labour Relations Board and most of our provincial Boards are protected in the determination of the matters coming before them by « privative clauses ». The author questions the effect of such clauses on the endeavours of the Boards and more directly on their real jurisdiction.